2009
DOI: 10.1021/jo900934j
|View full text |Cite
|
Sign up to set email alerts
|

One-step Synthesis of Fullerene Hydride C60H2 via Hydrolysis of Acylated Fullerenes

Abstract: The hitherto unexplored class of acylated fullerene compounds has been shown to be excellent C(60)H2 precursors. Upon a simple treatment with basic Al2O3, they are hydrolyzed quantitatively into C(60)H2. This key feature led to the development of a new, straightforward protocol for the selective synthesis of the simplest [60]fullerene hydride, C(60)H2. This protocol may offer an advantageous alternative to previously known methods for the synthesis of C(60)H2 allowing for a rapid access to C(60)H2 in good yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The selective synthesis of 1,2-C 60 H 2 in quantitative yield and high purity has been achieved through hydrolysis of acylated C 60 fullerene in the presence of basic Al 2 O 3 . 47 Products of thermal dehydrogenation of C 60 H 18 at 450-600 1C were studied by spectroscopic techniques. It was found that the complete dehydrogenation of the sample was not achieved, since peaks due to C-H vibrations were still observed even in samples heated at the highest temperatures.…”
Section: Production Separation and Properties Of Fullerenesmentioning
confidence: 99%
“…The selective synthesis of 1,2-C 60 H 2 in quantitative yield and high purity has been achieved through hydrolysis of acylated C 60 fullerene in the presence of basic Al 2 O 3 . 47 Products of thermal dehydrogenation of C 60 H 18 at 450-600 1C were studied by spectroscopic techniques. It was found that the complete dehydrogenation of the sample was not achieved, since peaks due to C-H vibrations were still observed even in samples heated at the highest temperatures.…”
Section: Production Separation and Properties Of Fullerenesmentioning
confidence: 99%
“…The retro-Bingel and retro-Diels–Alder (retro-DA) reactions are known as conventional methods for removal of addends on the fullerene cage (Figure a,b). Some reports have appeared on metal-catalyzed, base-assisted, and acid-promoted retro-reactions (Figure c). Our research group has been developing retro-reactions for synthesizing endohedral (hetero)­fullerenes, such as photochemical elimination of an SO unit, carbonyl coupling (using TiCl 4 /Zn, phosphite, or phosphine), and retro-DA reactions.…”
mentioning
confidence: 99%
“…20% yield). 8 The formation of this side-product (C 60 H 2 ) may be rationalized by the in situ conversion of 6a to C 60 H 2 , via a base catalyzed elimination of benzaldehyde from 6a. 9,10 In this case, C 60 À anion acts as a good leaving group by virtue of its increased electrophilicity.…”
mentioning
confidence: 99%